2005
DOI: 10.1081/pfc-200034327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sublethal Doses of 2,4-D, Simulating Drift, on Tomato Yield

Abstract: Tomato is considered one of the most sensitive crops regarding 2,4-D drift. In many cases, such susceptibility has led to important restrictions in the use of 2,4-D based products. Field experiments were carried out for two consecutive years in tomato, by applying sublethal doses of 2,4-D (ranging from 0.42 to 13.44 g a.i. ha(-1)) directly to plants, at different stages of growth, as a simulation of eventual drifts to the crop. The range of rates was based on the assumption of a 0.0625-2.0% drift level of a 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 5 publications
2
26
0
1
Order By: Relevance
“…Sublabel doses of 2,4-D reduced the potential fiber yield of cotton ( Gossypium hirsutum L.) by 32% to 62%, even with doses as low as 3.3 and 6.7 g ae ha −1 , respectively (Constantin et al 2007). Similar studies with other 2,4-D sensitive crops such as nontransgenic soybean (Johnson et al 2012) and tomato (Fagliari et al 2005) have shown extensive yield losses and deleterious effects. Cotton and soybean are highly variable in their responses to 2,4-D exposure, with growth stage and weather conditions at application identified as key factors (Egan et al 2014).…”
supporting
confidence: 65%
“…Sublabel doses of 2,4-D reduced the potential fiber yield of cotton ( Gossypium hirsutum L.) by 32% to 62%, even with doses as low as 3.3 and 6.7 g ae ha −1 , respectively (Constantin et al 2007). Similar studies with other 2,4-D sensitive crops such as nontransgenic soybean (Johnson et al 2012) and tomato (Fagliari et al 2005) have shown extensive yield losses and deleterious effects. Cotton and soybean are highly variable in their responses to 2,4-D exposure, with growth stage and weather conditions at application identified as key factors (Egan et al 2014).…”
supporting
confidence: 65%
“…To prevent contamination of neighboring plots, care was taken during application of the different glyphosate rates by covering perimeter field plots with 1 m high, framed cages covered with plastic sheeting (Fagliari et al, 2005). The cages remained on the plots for at least 5 min after glyphosate application to assure cessation of drift, and then removed.…”
Section: Glyphosate Applicationmentioning
confidence: 99%
“…morte do sistema radicular, epinastia das folhas, e outras alterações, induzem as plantas sensíveis à morte, caso ocorra deriva, quando de sua aplicação (Fagliari et al, 2005) e podem interferir no crescimento e no desenvolvimento de plantas nativas.…”
unclassified